Current Management and Progress in Radiotherapy for Small Cell Lung Cancer - Tjong, Michael C.; Mak, David Y.; Shahi, Jeevin; Li, George J.; Chen, Hanbo; Louie, Alexander V. (Frontiers in Oncology, 2020)
Radiotherapy (RT) and chemotherapy continue to be widely utilized in small cell lung cancer (SCLC) management. In most limited stage (LS)-SCLC cases, the standard initial therapy remains concurrent chemoradiotherapy (CRT), typically with an etoposide and platinum-based regimen. Hyperfractionated twice daily (BID) RT remains the standard of care, though conventional daily (QD) RT is now a viable alternative supported by randomized evidence. In LS-SCLC patients who experienced good response to CRT, prophylactic cranial irradiation (PCI) remains the standard of care. Brain imaging, ideally with MRI, should be performed prior to PCI to screen for clinically apparent brain metastases that may require a higher dose of cranial irradiation. Platinum doublet chemotherapy alone is the historic standard initial therapy in extensive stage (ES)-SCLC. Addition of immunotherapy such as atezolizumab and durvalumab to chemotherapy is now recommended after their benefits were demonstrated in recent trials. In patient with response to chemotherapy, consolidation thoracic RT and PCI could be considered, though with caveats. Emergence of hippocampal avoidance cranial irradiation and SRS in SCLC patients may supplant whole cranial irradiation as future standards of care. Incorporation of novel systemic therapies such as immunotherapies has changed the treatment paradigm and overall outlook of patients with SCLC. This narrative review summarizes the current state, ongoing trials, and future directions of radiotherapy in management of SCLC.